The construction of algebraic thinking by deaf students from a systematic review of the literature - Mikelândia Pereira da Silva; Evanilson Landim (Diversitas Journal, 2023)
This article aims to analyze the specificities of the construction of algebraic thinking by deaf students in the early and final years of elementary school through a Systematic Review. The specific objectives are: to identify the curricular recommendations - National Common Curricular Base (2017) and Pernambuco Curriculum (2019) related to the construction of algebraic thinking by elementary school students; to retrieve from the CAPES Periodicals Portal, Brazilian Digital Library of Theses (BDTD) and Google Scholar research that deals with the construction of algebraic thinking or the learning of mathematical knowledge by deaf students; to point out the recommendations of the literature on the development of algebraic thinking by deaf elementary school students. The study was guided by a systematic literature review methodology based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), which started with searches for articles and dissertations in the CAPES Periodicals Portal, BDTD and Google Scholar databases. A total of 2 727 studies were identified. After applying the inclusion or exclusion criteria, nine studies were selected for review. The results indicated that deaf students, like hearing students, present particularities in the construction of mathematical knowledge, especially in the Algebraic Unit Theme.